Unlearning and Relearning: A New Paradigm for Meaningful Indigenization of Educational Policies in Developing Nations - hasnah (Universitas Cahaya Prima, 2026)
Objectives: This systematic literature review examines how the concepts of 'unlearning and relearning' (Goodwin) can be reconceptualized as a new epistemological framework for the indigenization of educational policies in developing nations during the period 2000–2026, and how this framework can address the gap between global policy borrowing and meaningful local implementation. Methods: A systematic search was conducted across multiple databases (Scopus, ERIC, Web of Science) using keywords related to policy transfer, indigenization, unlearning, educational reform, and developing nations. The review synthesized 86 peer-reviewed sources published between 2000 and 2026, following PRISMA guidelines. Thematic analysis identified patterns in how developing countries conceptualize, implement, and adapt educational policies borrowed from global high-performing education systems. Findings: The literature reveals a critical paradox: while developing nations eagerly adopt policies from high-performing education systems (HPES), insiders within these systems consistently question their own effectiveness and doubt the transferability of their approaches. The concept of unlearning—strategic abandonment of ineffective policies regardless of their prestige—emerged as a crucial but underexplored dimension of meaningful policy indigenization. Three typologies of indigenization approaches were identified: (1) surface adaptation (cosmetic changes without substantive transformation), (2) systematic alignment (coherence across teacher education, curriculum, and classroom practice), and (3) epistemological reconstruction (redefining core educational values according to local contexts and knowledge systems). Developing nations in Southeast Asia demonstrated the greatest success when combining systematic alignment with epistemological reconstruction, supported by sustained political will and capacity building. Conclusion: The unlearning-relearning paradigm offers developing nations a theoretically grounded and empirically supported framework for moving beyond mere policy borrowing toward authentic indigenization. Rather than perpetually chasing international benchmarks, this approach enables countries to critically evaluate borrowed policies, abandon what proves ineffective in their context, and revitalize local knowledge systems in educational practices.